Effect of Highly Challenging Balance Training on Balance in Subjects with Chronic Parkinson's Disease. - Rajbanshi, Surendra Kumar; Chandrika P. C.; Joshi, Diker Dev (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Highly challenging balance training has been suggested to induce neuroplasticity in individuals with chronic Parkinson's disease (PD So, the present study aims to find the effect of highly challenging balance training on balance in subjects with chronic Parkinson's disease. Objective: To determine the effect of highly challenging balance training on balance in subjects with chronic Parkinson's disease. Method: 30 subjects between the age group of 45-60 years diagnosed with PD were included in the study and conveniently allocated to the single group after fulfilling inclusion and exclusion criteria. Baseline data like age, gender, Hoehn &Yahr stage was noted. Subjects underwent Highly Challenging Balance Training 45minutes per session 4 days/ week for 4 weeks. The pre and post test of balance was done by using Berg balance scales(BBS). Results: The highly challenging balance training on balance showed significant improvement in balance in post-test and also showed significantly improved balance. (p<0.05) in subjects with chronic Parkinson's disease. Conclusion: The result of the present study shows that highly challenging balance training significantly improved balance and showed promising transfer effects to everyday living. Long-term follow-up assessments can be done to further explore these effects. The results also show that regular training is required for the subjects to maintain progress.